Increased serum lysozyme activity in children with autism spectrum disorder - Montiel, Nola; Escalona, Milagros; Carrero, Yenddy; Urdaneta, Kendy Eduardo; Castillo, María Andrea; Martínez-Méndez, Dilia; Semprún-Hernández, Neomar (Investigación Clínica, 2018)
Ver Resumen PDF.